1987
DOI: 10.1177/019262338701500211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycine on the Induction of Orotic Aciduria and Urinary Bladder Tumorigenesis in the Rat

Abstract: The mechanism by which amino acids increase the cellular levels of orotic acid (OA) was investigated. Administration ofglycine (2.5 mmoles/100 g) to rats resulted in a 100-fold increase in urinary OA excretion, which was inhibited by pretreatment with cycloheximide or actinomycin D. The induction of OA synthesis from NH,Cl but not from carbamoylaspartate (CA) was inhibited by cycloheximide, indicating that the cycloheximide sensitive step was after the formation of ammonia and before the formation of CA. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It was found that the prolonged increase in orotic acid concentration in the body leads to lipid metabolism disorder and fatty infil tration of the liver [13,14], The role of orotic acid in promo tion of carcinogenesis has been recently reported [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the prolonged increase in orotic acid concentration in the body leads to lipid metabolism disorder and fatty infil tration of the liver [13,14], The role of orotic acid in promo tion of carcinogenesis has been recently reported [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium ions lead to the activation of pro-survival signaling, which induce toxicity and tumors in the animal body [ 141 – 143 ]. Oratic acid is produced in excess amounts during the metabolism of glycine, which might play a role as a tumor promoter [ 144 ]. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…This may discharge the variety of substances or other surgical procedures leading to urinary calculi in rats and/or mice. There were administered chemicals, acting directly (e.g., melamine) [40] or indirectly (i.e., through metabolites (diethylene glycol leading to calcium oxalate) [41] or through endogenous metabolic product (glycine leading to orotic acid) [42]) as well as the formation of urate calculi following surgical portocaval shunts in rats [43]). Also, in the rat vesciovaginal fistulas, like with the rat rectovaginal fistulas [10], the rat defect size/vaginal size ratio may be close to human disturbance (rectovaginal fistulas are con-˂ sidered complex if they are large ( 2.5 cm) [44]).…”
Section: Discussionmentioning
confidence: 99%